Influence of organism stimulation with bacterial lipopolysaccharide on nitric oxide production and metabolism in rat heart on the background of metabolic syndrome - Akimov, O. Ye.; Mykytenko, A. O.; Kostenko, V. O. (Modern medical technology, 2023)
Aim. The aim of the study was to establish the changes in nitric oxide production and metabolism in rat heart during combined influence of organism stimulation with bacterial lipopolysaccharide (LPS) and modeling of metabolic syndrome (MetS). Materials and methods. The study was conducted on 24 mature male Wistar rats weighing 200–260 g. Experiment lasted 60 days. The animals were divided into 4 groups of 6 animals each: control group, MetS group, LPS stimulation group, LPS + MetS group. MetS was reproduced by using a 20 % fructose solution as the only source of drinking water. LPS of Salmonella typhi was administered at a dose of 0.4 μg/kg intraperitoneally. Animals from LPS + MetS group received a 20 % fructose solution as the only source of drinking water and were administered LPS. In 10 % tissue homogenate of rat heart we studied: total activity of NO-synthases (NOS), activity of constitutive (cNOS) and inducible (iNOS) isoforms, activity of nitrate (NaR) and nitrite (NiR) reductases, concentration of peroxynitrites (ONOO-), nitrites, nitrosothiols and hydrogen sulfide. Results. Combination of MetS and stimulation of organism with LPS led to increase in total NOS activity by 32.72 % compared to control group. Activity of cNOS did not change compared to control group. Activity of iNOS increased by 33.76 %. Arginase activity decreased by 23.53 %. NaR activity and NiR activity were increased by 86.67 % and by 149.29 %, respectively. Combination of MetS and stimulation of organism with LPS led to decrease in nitrite and nitrosothiols concentration by 38.73 % and by 54.79 %, respectively. Under these conditions concentration of ONOOelevated by 398.0 % compared to control group. Concentration of H S decreased by 27.56 %. Conclusions. Combination of metabolic syndrome and stimulation of organism with bacterial lipopolysaccharide leads to prevalence of peroxynitrite formation during increased nitric oxide production NO-synthase-dependent and nitrate-nitrite-NO pathways in rat heart.